Stages of formation of city streets in the archaeological area of Afrasiyab in the IXth-XIIIth centuries (Genius Repository, 2023)
In this article, the formation of historical streets of Samarkand city in the 9th-13th centuries, the factors forming them, the boundaries of the city territory formed in the middle ages, and the processes of the formation of the street infrastructure are highlighted.